Economic Impacts and Challenges of Chinese Mining Industry: An Input–Output Analysis - Zhang, Binyuan; Yao, Jinge; Lee, Hyuck-Jin (Frontiers in Energy Research, 2022)
The mining industry (MI) has played a key role in ensuring a stable supply of minerals for industrial production and human survival. The Chinese government is implementing various policies to promote the MI and needs quantitative information on the economic role and effects of the MI. Thus, this article uses comprehensive and multi-period input-output (IO) analysis to investigate the roles of four mining sectors, including the entire mining sector in the Chinese national economy, from the period 2007–2017. To this end, three models are employed. First, the production-inducing effects, value-added creation effects, and wage-inducing effects of 1 dollar of production in the MI sector are analyzed using a demand-driven model. One dollar of production or investment in the sector causes 0.862–1.171 dollars of production, 0.271–0.333 dollar of value-added, and 0.106–0.125 dollar of wage, respectively. Second, by applying a supply-driven model, it is found that one dollar of supply shortage in the MI causes 4.383–5.949 dollars of production failure throughout the national economy. Third, by utilizing a price-side model, it is discovered that a 10% increase in the price of output of the MI raises the overall price level by 0.108%–0.171%. The results of this article were critical to enlighten policy-makers to forward ever-improvement on the MI and combine the MI within national economic system reform and planning, by offering a clear vision of how MI will affect the various sectors and the economic system as a whole.